Human immunodeficiency virus type 1 integrase: arrangement of protein domains in active cDNA complexes - Gao, Kui (Oxford University Press, 2001)
Early steps of retroviral replication involve reverse transcription of the viral RNA genome and integration of the resulting cDNA copy into a chromosome of the host cell. The viral-encoded integrase protein carries out the initial DNA breaking and joining reactions that mediate integration. The organization of the active integrase–DNA complex is unknown, though integrase is known to act as a multimer, and high resolution structures of the isolated integrase domains have been determined. Here we use site-specific cross-linking based on disulfide bond formation to map integrase–DNA contacts in active complexes. We establish that the DNA-binding C-terminal domain of one integrase monomer acts with the central catalytic domain from another monomer at each viral cDNA end. These data allow detailed modeling of an integrase tetramer in which pairs of trans interactions link integrase dimers bound to substrate DNA. We also detected a conformational change in integrase– DNA complexes accompanying cleavage of the viral cDNA terminus.